Peroxidase-like activity of nanocrystalline cobalt selenide and its application for uric acid detection - Zhuang QQ (Dove Medical Press, 2017)
Quan-Quan Zhuang,1 Zhi-Hang Lin,1 Yan-Cheng Jiang,1 Hao-Hua Deng,2 Shao-Bin He,1,3 Li-Ting Su,4 Xiao-Qiong Shi,2 Wei Chen2 1Department of Pharmacy, Affiliated Quanzhou First Hospital of Fujian Medical University, Quanzhou, 2Department of Pharmaceutical Analysis, School of Pharmacy, Fujian Medical University, Fuzhou, 3Department of Pharmacy, Quanzhou Infectious Disease Hospital, 4Department of Pharmaceutical Analysis, Quanzhou Medical College, Quanzhou, People’s Republic of China Abstract: Dendrite-like cobalt selenide nanostructures were synthesized from cobalt and selenium powder precursors by a solvothermal method in anhydrous ethylenediamine. The as-prepared nanocrystalline cobalt selenide was found to possess peroxidase-like activity that could catalyze the reaction of peroxidase substrates in the presence of H2O2. A spectrophotometric method for uric acid (UA) determination was developed based on the nanocrystalline cobalt selenide-catalyzed coupling reaction between N-ethyl-N-(3-sulfopropyl)-3-methylaniline sodium salt and 4-aminoantipyrine (4-AAP) in the presence of H2O2. Under optimum conditions, the absorbance was proportional to the concentration of UA over the range of 2.0–40 µM with a detection limit of 0.5 µM. The applicability of the proposed method has been validated by determination of UA in human serum samples with satisfactory results. Keywords: enzyme mimics, cobalt selenide, peroxidase-like activity, uric acid, human serum